KEPUASAN KERJA DIPENGARUHI OLEH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN KOMPENSASI PADA GURU SMP NEGERI 11 BALIKPAPAN - Bunga Wirayuda Busari, Umar; Hadiyatno, Didik; Cahyaning Putri Cipto, Rahajeng (Jurnal GeoEkonomi, 2025)
This study aims to examine the influence of Work Environment, Work Discipline, and Compensation on Teacher Job Satisfaction at SMP Negeri 11 Balikpapan. The study methodology applied is a quantitative study. This study uses purposive sampling, with a sample size of 65 individuals, consisting of 50 ASN individuals and 15 non-ASN individuals, which has a total sample of 50 ASN teachers at SMP Negeri 11 Balikpapan. The data collection method uses questionnaires. This study utilizes multiple linear regression as the analysis method and uses SmartPLS in data processing. The findings of this study indicate that work environment variables have an influence on the partial context on teacher job satisfaction at SMP Negeri 11 Balikpapan, while work discipline and compensation variables do not have an influence on the partial context on teacher job satisfaction.